Fine-scale spatial point patterns of Stipa breviflora population at different “Soil Island” habitat sizes in desert steppe - XUE Yi; WANG Xing; SONG Naiping; SUI Jinming; CHEN Juan (浙江大学学报. 农业与生命科学版, 2019)
Through long-term natural factors and human disturbance, the natural habitats of desert steppe become degradation and fragmentation, forming natural hard sierozem patches which were similar to islands in the extensive sandy desertified land, which were named as “Soil Island”. In order to study the influence of different “Soil Island” habitat areas on the spatial pattern of Stipa breviflora, we chose three large “Soil Island” (200-300 m2), three middle “Soil Island”(about 100 m2) and three small “Soil Island”(about 50 m2) habitats, and set one 2 m×2 m sample plot in each “Soil Island” in September 2016. The results showed that: 1) S. breviflora population was in the aging and declining stage in the all of “Soil Island” habitats, with very few young seedlings. 2) With the increase of the area of “Soil Island”, the content of clay silts in the 0-40 cm soil layer increased (P<0.05), and the content of fine sand in the 0-40 cm soil layer decreased (P<0.05), and the content of soil organic content (SOC) in different soil layers increased (P<0.05). 3) With the increase of the area of “Soil Island”, the ecological strategy of S. breviflora population changed. In the small “Soil Island”, the spatial patterns of S. breviflora aggregated mainly. But in the large “Soil Island” and middle “Soil Island”, the spatial patterns of S. breviflora were mainly random. 4) In each “Soil Island”, S. breviflora was the dominant species. With the increase of the area of “Soil Island”, the density of S. breviflora population increased first and then decreased, so we guessed that the optimum area of “Soil Island” habitat was about 100 m2. In summary, with the continuous reduce of the habitat areas of “Soil Island”, the spatial pattern of S. breviflora population changes from a random distribution to an aggregated distribution, and its population size and survival are under great threat, which indicates that the fragmentation of typical vegetation habitat will make population decline or even disappear. In the future, the integrity and continuity of the habitat should be guaranteed first, and then the size of the typical vegetation population could be guaranteed for the protection of the native vegetation of desert steppe.